Digital Wireless Spectrometer for Detection of Antibiotics in Milk - R, Aswatha.; S, Jaysree.B.; E, Isha.; R, Darshini.; D, Prasannaa Kumar.; M, Subash. (International Journal of Psychosocial Rehabilitation, 2020)
Antibiotic adulteration in milk due to medication given to cow is a major concern in recent days. Milk contaminated with antibiotic content should not be consumed as it causes a great harm to human immune system. So milk which contains traces of antibiotics is unfit for human consumption and it must be discarded. To determine presence of antibiotics in the milk digital spectrometer is used. Near Infra-red Spectrometer (NIR) is used to detect antibiotics in milk. Milk containing various fat percentage of 3% (Toned milk), 4.5% (Standardized milk) and 6% (Full cream milk) was diluted with water in the ratio of 90:10 (water:milk). Samples were categorized as unadulterated milk, milk with antibiotic Amoxycillin-1mg, and milk with antibiotic Cephalexin -1mg. Tensorflow is used to build a neural network to code, train and test the model. Accuracy of predicted values and trained values determines the presence of antibiotics in milk.